Reveal Cytotoxicity and Antigenotoxicity of Piper nigrum L. Ethanolic Extract and its Combination with Doxorubicin on CHO-K1 Cells - Nur Fitra Sari; Beni Lestari; Dian Saputri; Anisa Fauzia Ahsani; Ragil Anang Santoso; Ediati Sasmito; Edy Meiyanto (Indonesian Society for Cancer Chemoprevention, 2017)
Black pepper (Piper nigrum L.), one of the most popular Indonesian spices has been reported to possess various therapeutic effects. The aim of this study is to evaluate the cytotoxicity and antigenotoxicity of black pepper ethanolic extract (BPE) and its combination with doxorubicin (Dox) on CHO-K1 cells. Based on thin layer chromatographyanalysis, BPE contained piperine.Under MTT assay, BPE showed cytotoxic effect with the IC50 value of 68 μg/mL and performed synergism in combination with Dox. In vitro micronucleus test using Giemsa staining revealed that BPE did not cause morphological changes qualitatively on CHO-K1 cells at concentration of 8.5 μg/mL, whereas using flow cytometry analysis showed that BPE could decrease the number of micronucleus (MN) formation induced by doxorubicin. In addition, BPE reduced the ROS level on the CHO-K1 cells which observed by reactive oxygen species (ROS) intracellular assay. The decrease in ROS level indicated that the antioxidant activity of BPE contribute to the antigenotoxicity. Furthermore, molecular docking performed that piperine interacted with DNA Topoisomerase II with docking score of -80.68. Overall,BPE performed cytotoxic effect in single treatment, increased the cytotoxicity and reduced the genotoxicity of doxorubicin. Thus, BPE has potential to be developed further as co-chemotherapeutic and antigenotoxic agent.Keywords: Cytotoxic, genotoxic, Piper nigrum L., CHO-K1, micronucleus